Targeting Plasmodium Falciparum Dihydroorotate Dehydrogenase (PfDHODH) for the Development of New Antimalarials - Tuck, Reece Leighton (Stellenbosch : Stellenbosch University, 2026)
Thesis (MSc)--Stellenbosch University, 2026.